2018
DOI: 10.1136/bmjopen-2017-018834
|View full text |Cite
|
Sign up to set email alerts
|

Can virtual autopsy with postmortem CT improve clinical diagnosis of cause of death? A retrospective observational cohort study in a Dutch tertiary referral centre

Abstract: ObjectiveTo investigate whether virtual autopsy with postmortem CT (PMCT) improves clinical diagnosis of the immediate cause of death.DesignRetrospective observational cohort study. Inclusion criteria: inhospital and out-of-hospital deaths over the age of 1 year in whom virtual autopsy with PMCT and conventional autopsy were performed. Exclusion criteria: forensic cases, postmortal organ donors and cases with incomplete scanning procedures. Cadavers were examined by virtual autopsy with PMCT prior to conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
2
17
0
2
Order By: Relevance
“…These studies confirmed that PMCT has a significantly higher agreement on the cause of death than the clinical assessment alone [ 11 , 12 ]. Additionally, it was stated that the detection of cardiovascular diseases (e.g., coronary occlusion or stenosis, pulmonary embolism) is the major limitation of non-enhanced PMCT [ 7 , 10 , 12 ]. This limitation also explains why post-mortem angiography is a promising technique in the field of post-mortem research [ 4 , 13 ].…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…These studies confirmed that PMCT has a significantly higher agreement on the cause of death than the clinical assessment alone [ 11 , 12 ]. Additionally, it was stated that the detection of cardiovascular diseases (e.g., coronary occlusion or stenosis, pulmonary embolism) is the major limitation of non-enhanced PMCT [ 7 , 10 , 12 ]. This limitation also explains why post-mortem angiography is a promising technique in the field of post-mortem research [ 4 , 13 ].…”
Section: Introductionsupporting
confidence: 56%
“…Among these possibilities, post-mortem computed tomography (PMCT) is considered to be the most feasible imaging modality because it is fast and widely available. So far, three clinical studies have shown that PMCT is in agreement with autopsy on the cause of death of hospitalized patients in 64–74% of all cases [ 10 , 11 , 12 ]. These studies confirmed that PMCT has a significantly higher agreement on the cause of death than the clinical assessment alone [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In high-income countries, imaging-based methods have been proposed as an alternative to the CDA, but the high costs and the high level of expertise required are major drawbacks for their implementation, particularly in low- and middle-income countries (LMIC). Moreover, these imaging-based methods could be insufficient for the identification of infectious CoD [10], presumably more frequent in LMIC. Therefore, innovative methods are necessary in LMIC, where most premature deaths occur, and robust mortality data are poor [1].…”
Section: Introductionmentioning
confidence: 99%